Correction: 12 Novel clonal groups of Leptospira infecting humans in multiple contrasting epidemiological contexts in Sri Lanka. - Dinesha Jayasundara; Indika Senavirathna; Janith Warnasekara; Chandika Gamage; Sisira Siribaddana; Senanayake Abeysinghe Mudiyanselage Kularatne; Michael Matthias; Jean-François Mariet; Mathieu Picardeau; Suneth Agampodi; Joseph M Vinetz (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pntd.0009272.].